2016
DOI: 10.1037/edu0000042
|View full text |Cite
|
Sign up to set email alerts
|

Creating birds of similar feathers: Leveraging similarity to improve teacher–student relationships and academic achievement.

Abstract: When people perceive themselves as similar to others, greater liking and closer relationships typically result. In the first randomized field experiment that leverages actual similarities to improve real-world relationships, we examined the affiliations between 315 9th grade students and their 25 teachers. Students in the treatment condition received feedback on 5 similarities that they shared with their teachers; each teacher received parallel feedback regarding about half of his or her 9th grade students. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(152 citation statements)
references
References 55 publications
(92 reference statements)
2
123
0
Order By: Relevance
“…Given these findings and findings from the social influence literature (MacKinnon et al, 2011), faculty mentors and mentoring programs should consider making explicit efforts to foster student’s perceptions of similarity across a wide variety of topics. Recent research with teachers and students indicates that explicit efforts to identify similarities on a wide variety topics (e.g., ideal field trip, important qualities in friends, family in the military; Gehlbach et al, 2016) engendered perceptions of similarity, which in turn, benefited student’s motivation and performance, particularly for URMs (Gehlbach et al, 2016). Faculty members from majority groups who are mentoring URM students may wish to set aside time early in the relationship for a “getting to know each other” meeting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given these findings and findings from the social influence literature (MacKinnon et al, 2011), faculty mentors and mentoring programs should consider making explicit efforts to foster student’s perceptions of similarity across a wide variety of topics. Recent research with teachers and students indicates that explicit efforts to identify similarities on a wide variety topics (e.g., ideal field trip, important qualities in friends, family in the military; Gehlbach et al, 2016) engendered perceptions of similarity, which in turn, benefited student’s motivation and performance, particularly for URMs (Gehlbach et al, 2016). Faculty members from majority groups who are mentoring URM students may wish to set aside time early in the relationship for a “getting to know each other” meeting.…”
Section: Discussionmentioning
confidence: 99%
“…Although a convergence of data show the importance of perceived similarity on the quality of the mentoring relationship (Eby et al, 2013), little research within the mentoring literature has shed light on the factors that engender high levels of perceived similarity. However, experimental and correlational research in the social influences literature indicates that diverse types of similarities (e.g., name, physical, musical, hobbies, or values) can engender higher perceptions of similarity and even trivial similarities can have a positive impact on the quality of the relationship (Boer, Fischer, Strack, Bond, Lo, & Lam, 2011; Gamer, 2005; Gehlbach, Brinkworth, King, Hsu, McIntyre, & Rogers, 2016; MacKinnon, Jordan, & Wilson, 2011). For example, a recent randomized field study with 9 th graders manipulated the disclosure of five shared similarities between students and teachers on a wide variety of topics (e.g., similar choice in field trip location [museum, sports event, music concert, or hiking]; Gehlbach et al, 2016).…”
Section: Similarity and Mentoring Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention led to an increase in science grades for students in both struggle treatments. Moreover, Gehlbach, et al (2016) found that providing teachers and students with information about similarities in their values, interests etc. led to improved grades.…”
Section: Social Belonging Identity Activation and Mindset Nudgesmentioning
confidence: 99%
“…However, psychological interventions can also make social worlds easier to navigate. Racial-minority students can be held back by teachers' feelings of dissimilarity to them (28). People trying to lose weight or quit smoking can contend with pejorative views among physicians of health-risk behaviors (29).…”
Section: Response or Themementioning
confidence: 99%